ANALISIS KESADARAN DAN SIKAP MAHASISWA TERHADAP KEBOCORAN DATA PRIBADI DI ERA DIGITAL - Camilia Indah Novia Taufik; Agus Juhana (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2025)
This research investigates the "privacy paradox," a phenomenon in which individuals, particularly university students, express concerns about data privacy but fail to implement effective measures to protect their personal information. The study seeks to identify key factors influencing students' awareness and behaviors concerning personal data security while proposing strategies to improve their knowledge and practices in the face of accelerating digital advancements. Employing a Systematic Literature Review using the PRISMA method, this research analyzed articles published between 2014 and 2023 to explore pertinent themes. The results indicate that students frequently disregard privacy policies and security protocols, leaving them susceptible to data breaches. Although they articulate concerns about threats from social media, university networks, and smartphones, their actions often contradict these concerns. This inconsistency arises from limited understanding of data collection processes and a perception of ineffectiveness in privacy protection efforts. The study underscores the importance of educational initiatives, such as cybersecurity training, phishing awareness programs, and the integration of advanced security technologies like blockchain and encryption. Furthermore, the enactment of Indonesia's Personal Data Protection Bill (PDP Bill) is identified as a critical step toward strengthening the legal framework for data security. Collectively, these measures aim to mitigate privacy risks and enhance students' compliance and awareness in safeguarding their personal data.